A behavioural investigation of power and gender heterogeneity in operations management under uncertainty. Issue 6 (13th January 2020) - Villa, Sebastián; Castañeda, Jaime Andrés
Abstract : Purpose: The paper aims to explore how power and gender influence decision making in an operational and risky context. Design/methodology/approach: The authors run a laboratory experiment. The experimental factors are power and operational profitability. Power is manipulated using an episodic priming task, while profitability, by changing a newsvendor-type product's procurement cost. Participants' risk attitude is captured using a risk lottery. Findings: Participants deviate from the optimal order regardless of the power condition and their risk profile. Risk-seeking women order consistently more than risk-seeking men, which allow women to offer a higher service level. In the low-profit condition, men prefer to make more conservative decisions, which allow them to place orders that are closer to the economical benchmark, where both men' induced power and the risk-seeking tendencies from both genders play a role. Behavioural models in the high-power condition explain the observed differences in ordering behaviours. Originality/value: This paper provides behavioural research to explore how differences in power and gender, and their links with risky decision making, influence decision making in an uncertain operations management context, representing thus an important departure from mainstream studies.